1988
DOI: 10.1093/schbul/14.2.323
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistencies in Paranoid Functioning, Premorbid Adjustment, and Chronicity: Question of Diagnostic Criteria

Abstract: Despite the widely held belief that paranoid behavior is associated with good premorbid adjustment, low chronicity, and high current functioning in psychiatric inpatients, inconsistencies in the literature suggest that supportive evidence may be an artifact of the measurement model commonly used to index paranoid status. In a sample of 497 nonorganic inpatients selected from 19 treatment units, paranoid behavior, when measured by a dimensional/cumulative model, was not found to indicate higher functioning and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 45 publications
6
25
0
Order By: Relevance
“…For example, Sorensen et al [63] evaluated the relative merits of a dimensional versus subtype approach to paranoia. For example, Sorensen et al [63] evaluated the relative merits of a dimensional versus subtype approach to paranoia.…”
Section: Common Statistical Evidence For Subtypesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Sorensen et al [63] evaluated the relative merits of a dimensional versus subtype approach to paranoia. For example, Sorensen et al [63] evaluated the relative merits of a dimensional versus subtype approach to paranoia.…”
Section: Common Statistical Evidence For Subtypesmentioning
confidence: 99%
“…Finally, it is also certainly the case that using a variable dimensionally versus dichotomously might yield differing or even opposite results. For example, Sorensen et al [63] evaluated the relative merits of a dimensional versus subtype approach to paranoia. He found that when paranoia was measured dimensionally, those with more paranoid symptomatology were lower on other measures of current functioning, a finding inconsistent with other literature.…”
Section: Common Statistical Evidence For Subtypesmentioning
confidence: 99%
“…So far, no indices for localizable cerebral dysfunctions in paranoid disorders have been found in neuropsychological studies, although the results are heterogeneous, probably at least in part due to different diagnostic criteria, the influence of medication, artifacts produced by spot sampling, as well as different neuropsychological tests. Regarding the problem of inclusion and exclusion criteria, Sorensen et al [65] pointed out that these factors may artificially increase or decrease the number of paranoid or non-paranoid test subjects, thereby also skewing the test data for group comparisons. Bornstein et al [57] also showed that between-group differences in cognitive performance could be due to confounding variables (see above).…”
Section: Neuropsychological Findingsmentioning
confidence: 99%
“…However, as emphasized by Sorensen, Paul, and Mariotto (1988), the model behind, for example, the DSM-III diagnosis of paranoid schizophrenia is a predomi-nance model. In such a model a diagnosis is based principally on the predominance of paranoid symptoms over other symptoms rather than on the intensity of paranoid thought and behavior as such.…”
Section: Sm~iri Stef~nsson and Thorgilssonmentioning
confidence: 99%
“…In such a model a diagnosis is based principally on the predominance of paranoid symptoms over other symptoms rather than on the intensity of paranoid thought and behavior as such. Of course, paranoid symptoms are frequent in other types of schizophrenia and, as argued by Sorensen et al (1988), predominance models largely neglect this wider significance of paranoid symptoms. Thus, it is not evident that a paranoia measure should necessarily be strongly related to the paranoid subtype to be valid.…”
Section: Sm~iri Stef~nsson and Thorgilssonmentioning
confidence: 99%